2007
DOI: 10.1002/app.25916
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of crosslinked superabsorbent carboxymethyl cellulose/acrylamide hydrogels through electron‐beam irradiation

Abstract: A study on the possibility of the preparation of superabsorbent hydrogels based on crosslinked carboxymethyl cellulose polymer and acrylamide monomer through electron-beam irradiation was carried out. The effects of the irradiation dose and polymer-monomer compositions on the crosslinking density were studied. The hydrophilic properties of the superabsorbent hydrogels were identified by the swelling percentage. The prepared hydrogels had higher swelling in distilled water than in salt solutions. Moreover, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(53 citation statements)
references
References 26 publications
(22 reference statements)
0
49
0
1
Order By: Relevance
“…In previous studies, the effect of absorbed dose (Furusawa et al 2005) on gel properties was also thoroughly examined, but the effect of solution concentration was studied for a few derivatives only (Pekel et al 2004, Yoshii et al 2003. It is difficult to compare the results of gel fraction (GF) studies, due to the significantly differing methods of removing the sol, such as immersion in water for 2 days (Liu et al 2005), for 2 weeks (Furusawa et al 2005) or extraction in boiling water (Ibrahim et al 2007). The time dependence of swelling was determined in numerous studies, but swelling kinetic models were proposed only for hydroxypropylcellulose gels (Wach et al 2002), while the mechanism of water diffusion into the polymer network was not examined at all.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the effect of absorbed dose (Furusawa et al 2005) on gel properties was also thoroughly examined, but the effect of solution concentration was studied for a few derivatives only (Pekel et al 2004, Yoshii et al 2003. It is difficult to compare the results of gel fraction (GF) studies, due to the significantly differing methods of removing the sol, such as immersion in water for 2 days (Liu et al 2005), for 2 weeks (Furusawa et al 2005) or extraction in boiling water (Ibrahim et al 2007). The time dependence of swelling was determined in numerous studies, but swelling kinetic models were proposed only for hydroxypropylcellulose gels (Wach et al 2002), while the mechanism of water diffusion into the polymer network was not examined at all.…”
Section: Introductionmentioning
confidence: 99%
“…The study of superabsorbent polymers (SAPs) has received a great deal of attention due to their application in many fields, such as agriculture and horticulture [1], sanitary goods [2], drug delivery [3,4], artificial implant [5], waste-water treatment [6], biomedical area [7], and so on. The excellent ability to absorb water and/or heavy-metal ions is related to their three-dimensional crosslinked structure [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Certain studies (Liu et al 2005a;Ibrahim et al 2007;Pourjavadi et al 2007b;Akar et al 2012;Shi et al 2013;Wang et al 2008Wang et al , 2013 showed a distinct maximum swelling at neutral pH; a possible explanation for this finding is that increasing amounts of ions must be added to such a system to achieve pH values significantly different from 7; such ions would be expected to have the same effect corresponding to the previous subsection (Effects of Salinity). Odd results, roughly opposite to those just cited, were obtained by Varaprasad et al (2011), though no explanation was given.…”
Section: Effect Of Phmentioning
confidence: 93%
“…Considerable research has been devoted to the development of copolymers in which CMC is reacted with acrylic monomers and various crosslinking agents to form SAPs (Kuwabara and Kubota 1996;Pourjavadi and Mahdavinia 2005;Pourjavadi and Ghasemzadeh 2006;Abd El-Mohdy 2007;Ibrahim et al 2007;Pourjavadi et al 2007aPourjavadi et al -b, 2008Pourjavadi et al , 2009Pourjavadi et al , 2010Suo et al 2007;Ali et al 2008;Chen et al 2008;Yang et al 2009;El-Din et al 2010;Feng et al 2010a;Lin et al 2010;Bao et al 2011;Eldin et al 2011;Huang et al 2011;Liu et al 2011;Shu et al 2011;Varaprasad et al 2011;Wang et al 2011c). Water absorbency values generally in the range of 40 to 1400 g/g have been reported in such studies, with the highest value reported by Pourjavadi et al (2008).…”
Section: Copolymers Of Cmc By Reaction With Monomersmentioning
confidence: 99%